Foreign direct investment and regional inequality: A panel data analysis - Christian Lessmann (Center for Economic Studies and ifo Institute (CESifo), 2012)
Foreign direct investments (FDI) are an important determinant of economic growth. Coun-tries try to attract mobile capital in order to foster economic development, albeit FDI might increase regional inequality since the many different regions of a country usually do not receive FDI in equal measure. A conflict emerges between efficiency and redistribution. The aim of this paper is to investigate the impact of foreign direct investment on regional inequalities. First, the Chinese case is analyzed as an introductory example. FDI has increased regional inequalities in China after the economic reforms in the 1980s, but the effect has vanished - if not reversed - since the end of the 1990s. Second, the major contribution of the paper is to analyze cross-country time-series data on FDI and regional inequalities. Based on a unique panel data set of regional inequalities covering 55 countries at different stages of development, I find net FDI inflows to increase regional inequality in low and middle income countries, while there are no negative redistributional consequences in high income economies. The analysis also shows that the observable higher mobility of individuals in high developed countries as well as government policies are likely to mitigate the negative redistributional impact of FDI on regional inequality. Insofar, the cross-country data supports the lessons from the Chinese case with respect to the reducing effect development has on the negative impact from FDI on regional inequality.
Keywords: O57; R12; F43; 330; regional inequality; foreign direct investment; panel data; Direktinvestition; Ausländisch; Regionale Disparität; Regionale Einkommensverteilung; China; Welt